Epidemiology of Cardiopulmonary Arrest and Outcome of Resuscitation in PICU Across China: A Prospective Multicenter Cohort Study - Ding, Xin; Liu, Gang; Qian, Suyun; Zeng, Jiansheng; Wang, Ying; Chu, Jianping; Chen, Qing; Chen, Jianli; Duan, Yuanyuan; Jin, Danqun; Huang, Jiaotian; Lu, Xiulan; et al. (Frontiers in Pediatrics, 2022)
Aim: To investigate the epidemiology and resuscitation effects of cardiopulmonary arrest among critical ill children and adolescents during PICU stay across China. Methods: A prospective multicenter study was conducted in 11 PICUs in tertiary hospitals. Critical ill children aged from 1 month to 18 years with cardiopulmonary arrest, received cardiopulmonary resuscitation (CPR) and consecutively hospitalized in PICU during the study period (December 1st, 2017 to October 31st, 2018) were enrolled. Data was collected and analyzed using the "in-hospital Utstein style". Neurological outcome was assessed with the pediatric cerebral performance category among children who survived. Results: Total of 372 children among 11588 cases (3.2%) in PICU had cardiopulmonary arrest during PICU stay with 281 (75.5%) received CPR and 91（24.5%）required “Do Not Resuscitation”. Cardiopulmonary disease was the most common reason for cardiopulmonary arrest, with respiratory system 27.8% and circulatory system 19.6%. The most frequent initial heart rhythm was bradycardia (79%). About 170 (60.3%) of children had recovery of spontaneous circulation, 91 (37.4%) cases survived to hospital discharge, 28 (11.5%) cases survived 6 months after discharge and 19 (7.8%) survived 1 year after discharge. Among the 91 children who remained alive when discharge, 47.2%（43/91）got a good PCPC score (1-3). The results of regression analysis revealed that CPR duration, epinephrine frequency correlated with ROSC, while CPR duration, original diseases, CPR times, ventricular tachycardia/ventricular fibrillation, epinephrine frequency was associated with survival to discharge to hospital. Conclusion: The prevalence of cardiopulmonary arrest in critical ill children and adolescent is relatively high. The long-term prognosis of children and adolescents survived cardiopulmonary resuscitation need further improvement. CPR duration and frequency of epinephrine use are independent factors for the effect of ROSC.